Existence of exact Walrasian equilibria in non convex economies - Antonio D'Agata (Kiel Institute for the World Economy (IfW), 2011)
The existence of an exact Walrasian equilibrium in non convex economies is still a largely unexplored issue. In this paper an existence result for exact equilibrium in non convex economies is provided by following the almost-near approach introduced by Postlewaite and Schmeidler for convex economies. More precisely, we show that for any non convex economy there is a set of perturbed economies with the same number of agents exhibiting an exact Walrasian equilibrium; moreover as the number of agents tends to infinity the perturbed economies can be chosen as much close as we like to the original one.
Keywords: C62; D51; 330; exact Walrasian equilibrium; non convex economies; perturbed economies